The moderating role of sustainable development goals in reviving the economy through green initiatives - Tang, Honglei; Maqbool, Asifa; Khan, Ali Junaid; Ul Hameed, Waseem; Batool, Hafsah; Ahmed, Tanveer (Frontiers in Environmental Science, 2023)
The Ukrainian economic crisis began with the start of the war and grew over time. This is because trade between countries was spread out because of problems with the supply chain. However, the energy sector in Ukraine is largely disturbed by this armed conflict. The purpose of this study was to test the impact of infrastructure damage, trade sanctions, the economic crisis, and energy investments in green energy in Ukraine through the lens of sustainable development goals (SGDs). The data is collected from the Ukrainian public, and the sample size for this research is 384. This research has used the structural equation modeling method by using Smart PLS 3 for data analysis. The findings of the study suggest that a green energy transition is possible when the Ukrainian government works on SDGs to manage the economic crisis and increases investments in the energy sector. The moderation of SGDs is considered a way forward for development in Ukraine. The novelty of this research is based on its framework, which is a new addition to a piece of knowledge. This research has extended knowledge by presenting new relationships related to the green energy transition. The limitations of this research are presented in conjunction with future directions that are a reliable way for scholars to contribute further to this area of research.